Extracellular CIRP induces acute kidney injury via endothelial TREM-1 - Siskind, Sara; Zhang, Fangming; Brenner, Max; Wang, Ping (Frontiers in Physiology, 2022)
Introduction: Acute kidney injury is associated with elevated serum levels of extracellular cold-inducible RNA-binding protein (eCIRP), a damage-associated molecular pattern released during ischemia/reperfusion injury, hemorrhagic shock, and sepsis. It is unknown if circulating eCIRP and eCIRP-induced activation of receptor triggering receptor expressed on myeloid cells-1 (TREM-1), expressed on endothelial cells, play an important role in the pathogenesis of AKI. Methods: Male B6 wild-type (WT) and TREM-1-/- mice were subjected to intravenous injection of recombinant murine (rm) CIRP. Serum, urine, and renal tissue were collected 6 hours later for analysis. Additionally, primary human renal glomerular endothelial cells (HRGEC) were stimulated in vitro with rmCIRP after pretreatment with M3, a novel inhibitory peptide of TREM-1, or vehicle. Supernatants and cells were collected 20 hours after stimulation. Results: After injection with rmCIRP, WT mice had a significant increase in serum levels of BUN, creatinine, and NGAL compared to control. Additionally, NGAL was significantly increased in the urine of rmCIRP-injected mice, suggesting that circulating eCIRP can directly induce AKI. The levels of TREM-1 mRNA in the kidneys, as well as soluble (s) TREM 1 released into the serum and urine, were significantly increased in rmCIRP-injected mice. TREM-1-/- mice injected with rmCIRP had attenuated AKI, indicated by significantly decreased serum BUN, creatinine, and NGAL, and renal mRNA expression of NGAL and KIM-1 compared to WT mice. TREM-1-/- mice also had attenuated endothelial activation, with decreased mRNA and protein expression of ICAM-1 in renal tissue. HRGEC stimulated with rmCIRP in vitro had significant increases in cytokine production and sTREM-1 release, which was attenuated in cells treated with M3. Conclusion: Activation of renal TREM-1 with circulating eCIRP is sufficient to cause AKI. Elevated levels of eCIRP may be critical for the development of AKI under conditions such as ischemia/reperfusion injury, hemorrhagic shock, and sepsis. Mice deficient in the TREM-1 receptor have attenuated AKI and reduced endothelial cell activation after injection of rmCIRP. TREM-1 inhibition with M3 attenuates HRGEC activation after eCIRP stimulation. Targeting eCIRP activation of TREM-1 may provide a novel and effective treatment for AKI.